Strategi Komunikasi Bisnis BritCham Indonesia dalam Mewadahi Kerjasama Perdagangan Bilateral Inggris dan Indonesia: (Studi Deskriptif Data Kualitatif pada BritCham Business Centre melalui Business Support Services) - Dena Rizky Syahira; Tresna Wiwitan (UNISBA Press, 2022)
Abstract. Indonesia is a country that has a lot of natural wealth but still needs help from other countries to be able to develop optimally, therefore, Indonesia cooperates with other countries, one of which is the UK. This bilateral trade cooperation relationship between the UK and Indonesia encourages researchers to conduct research on